(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
نفِّذ التهجين نصف التبادلي بين ست سلالات مرباة ذاتيّاً، في قسم بحوث الذرة التابع للهيئة العامّة للبحوث العلميّة الزراعيّة بدمشق، في الموسمين الزراعيين 2010- 2011، بهدف تقدير القدرة العامة والخاصة على التوافق وكذلك قوّة الهجين لصفات الغلة الحبية (طن/هكتار), ارتفاع العرنوس (سم), طول وقطر العرنوس (سم)، وزن100حبة (غ)، وصفة الإزهار المؤنث (يوم). وخلصت النتائج إلى ما يلي: كان تباين السلالات والهجن عالي المعنوية لكلِّ الصفات المدروسة، دلالة على التباعد الوراثي بين السلالات الأبوية. وأظهرت القدرة العامة والخاصة على التوافق تبايناً عالي المعنوية في كلّ الصفات، حيث يبيّن ذلك مساهمة كلٍّ من الفعل الوراثي التراكمي واللاتراكمي في وراثة كل هذه الصفات. بينت نسبة تباين القدرة العامة على تباين القدرة الخاصة σ2GCA/σ2SCAسيطرة الفعل الوراثي التراكمي على وراثة جميع الصفات المدروسة ماعدا صفتي وزن100حبة والغلة الحبية التي سيطر عليهما الفعل الوراثي اللاتراكمي. أظهرت جميع الهجن قوّة هجين إيجابية عالية المعنوية قياساً لمتوسط وأفضل الأبوين لجميع الصفات المدروسة. أبدت السلالات (CML.317)، (CML.371)، (CML.373)، (CML.367)، قدرة عامة موجبة وعالية المعنوية على التوافق لصفة الغلة الحبية. أظهرت سبعة هجن قدرة خاصة جيدة على التوافق لصفة الغلة الحبية كان أفضلها الهجين (CML.317×CML.371). A half diallel set of crosses among six inbred lines of maize were evaluated at the Maize Researches Department (G.C.S.A.R.) Damascus. Governorate, during 2010 and 2011 to study heterosis and combining ability components for grain yield(ton /hec), ear height(cm) date, ear length(cm), ear diameter(cm), 100-kernels weight (g), and silking(days). Inbred lines, crosses, general (GCA) and specific (SCA) combining ability mean squares were highly significant for all studied traits, indicated the genetic variance among lines. The ratios were detected for all studied traits and showed that additive gene action. except 100-kernels weight and grain yield which showed predominance of non-additive gene action. Heterosis percentage for all studied traits was significant compared with mid and better parents. GCA effects showed that the lines CML.317, CML.371, CML.373 and CML.367 were good general combiners for grain yield. SCA effects showed that seven hybrids were the best F1 cross combinations such as (CML.317×CML.371) for grain yield.